Waste Collection Vehicle Routing Problem with TimeWindows for Route Optimization of Garbage Transport Vehicles - Evi Yuliza; Bambang Suprihatin; Putra Bahtera Jaya Bangun; Fitri Maya Puspita; Indrawati; Sisca Octarina (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
The waste collection vehicle routing problem with time windows is an optimization problem on the route of the waste transport vehicle which aims to determine the route of the vehicle by considering the travel time and windows. Garbage transport vehicles transport garbage in several work areas. This affects the optimal time and distance. The working hours of the garbage collectors are divided into two parts. The first working hours are 07.00 - 11.00 West Indonesian Time (WIT) and 16.00-20.00 WIT. The cleaning staff has a break of 5 hours. This study aims to optimize the route of waste transportation vehicles in the problem of transporting waste so as to minimize travel time and distance. Waste collection vehicle routing problem with time windows on determining the route of a garbage transport vehicle which is simulated on the problem of transporting garbage in the city of Palembang. The waste collection vehicle routing problem with the time windows model is solved with an exact approach using LINGO software. The results of this study indicate that the proposed optimization model provides optimization of the route of the garbage transport vehicle, the total travel time, and break time of the cleaning staff.